Antimicrobial activity of chitosan-silver nanoparticles made from jewelry industry silver waste - Perdana, Muhammad Iqbal; Kusuma, Ikhwan Yuda; Sunu Brams Dwandaru, Wipsar; Yulianti, Evy; Tóth, Barbara; Csupor, Dezső; Takó, Miklós; Vágvölgyi, Csaba (Archives of Biological Sciences, 2024)
Paper description: Novel chitosan-silver nanoparticles (CS-AgNPs) have been synthesized from recycled silver. CS-AgNPs were examined as antimicrobial agents based on the inhibition zone, MIC50, and microbial growth inhibition. CS-AgNP effectively inhibited the growth of coli, S. aureus, and C. albicans. CS-AgNP-based products may be promising in local antibacterial therapy. Abstract: Local management of bacterial infections is challenging. The antimicrobial effect of silver has long been recognized, but its use is limited due to its expensive nature and reduced applicability in liquids. This study aimed to synthesize chitosan-silver nanoparticles (CS-AgNPs) from reusable silver waste of the jewelry industry and investigate their antimicrobial properties against pathogenic microorganisms. X-Ray diffraction (XRD) analysis was used to confirm the crystalline structure of the recycled silver, with a strong diffraction peak observed at 2θ=38.60°. Agar disk diffusion showed inhibitory effects for CS-AgNPs on the growth of Escherichia coli, Staphylococcus aureus, and Candida albicans that depended on the concentration of AgNO3 solution used for preparation. In these tests, S. aureus was more susceptible to the treatment than E. coli and C. albicans. The CS-AgNP inhibited the growth of tested microorganisms with minimum inhibitory concentration (MIC50) values between 1.7 and 4.25 mg/mL. These findings highlight the potential of CS-AgNPs as effective antimicrobial agents. The use of waste materials in nanoparticle synthesis in this research offers a promising approach for sustainable and eco-friendly nanotechnology.